ANALISIS PENGARUH CAR, LOAN, GDP DAN INFLASI TERHADAP PROFITABILITAS BANK DI INDONESIA - Sorongan, Fangky A. (Jurnal Akuntansi, 2017)
This study aims to examine the relationship between bank profitability and the factors that affect the level of profitability of the banking system in Indonesia. The population and samples used in this study are ten banks with the largest total assets in Indonesia such as BRI, Bank Mandiri, BCA, BNI, CIMB Niaga, BTN, Bank Panin, Bank Permata, Maybank and Bank Danamon, with observation year 2012 until by 2015. Dependent variable is profitability represented by return on asset (ROA), while four independent variables are CAR (capital adequacy ratio), LOAN, GDP (gross domestic product) and inflation. The result of regression analysis shows that CAR, LOAN, GDP have important contribution significantly to profitability (ROA) in bank in Indonesia, while the inflation variable has no significant and negative effect on profitability (ROA).